Stability of a mathematical model of HIV/AIDS considering treatment and the impact of media coverage - Gonzales Moreno, Evelyn Katherine (2021)
A mathematical model is proposed to study the dynamics of the spread of HIV/AIDS with treatment considering media coverage. The subpopulations involved in the study are; susceptible individuals, slow-latency infected individuals, fast-latency infected individuals, symptomatic individuals undergoing treatment, and finally individuals with AIDS. We consider a system of ordinary differential equations that let us to understand the dynamics of the spread of HIV/AIDS, taking into account two non-linear incidence rates that show the influence of media coverage as a disease control. We establish conditions for the stability of this model. The result enables us to evaluate the media coverage impact on the dynamics of the disease. Finally, we show a numerical simulation analysis of the model and a sensitivity analysis corresponding to the parameters.